2017
DOI: 10.1158/1078-0432.ccr-16-2818
|View full text |Cite
|
Sign up to set email alerts
|

A Phase 2/3 Multicenter, Randomized, Open-Label Study to Compare the Efficacy and Safety of Lenalidomide Versus Investigator's Choice in Patients with Relapsed or Refractory Diffuse Large B-Cell Lymphoma

Abstract: Purpose: Randomized, multicenter, open-label, phase 2/3 trial investigating lenalidomide versus investigator's choice (IC) in relapsed/refractory diffuse large B-cell lymphoma (DLBCL).Experimental Design: Patients with DLBCL who received 2 prior therapies were stratified by DLBCL subtype [germinal center B-cell (GCB) vs. non-GCB; determined by immunohistochemistry (IHC)] and then randomized 1:1 to lenalidomide (25 mg/day, 21 days of 28-day cycle) or IC (gemcitabine, rituximab, etoposide, or oxaliplatin). Cross… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
121
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 142 publications
(125 citation statements)
references
References 38 publications
(47 reference statements)
4
121
0
Order By: Relevance
“…ABC-DLBCL patients treated with lenalidomide when compared with GCB patients showed greater improvements in overall response rate (45.5% vs 21.4%), progression-free survival (82 weeks vs 13.2 weeks), and overall survival (108.4 weeks vs 30 weeks). 26 In contrast to lenalidomide, CC-122 appears to possess broader cell autonomous activity than lenalidomide, spanning both the ABC-and GCB-DLBCL subtypes. Although the precise mechanism is not fully known, we suggest 2 possibilities to explain the differential activity of CC-122 and lenalidomide.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ABC-DLBCL patients treated with lenalidomide when compared with GCB patients showed greater improvements in overall response rate (45.5% vs 21.4%), progression-free survival (82 weeks vs 13.2 weeks), and overall survival (108.4 weeks vs 30 weeks). 26 In contrast to lenalidomide, CC-122 appears to possess broader cell autonomous activity than lenalidomide, spanning both the ABC-and GCB-DLBCL subtypes. Although the precise mechanism is not fully known, we suggest 2 possibilities to explain the differential activity of CC-122 and lenalidomide.…”
Section: Discussionmentioning
confidence: 99%
“…[24][25][26] Our previous preclinical studies also demonstrated that lenalidomide had preferential antiproliferative activity in ABC-DLBCL cell lines vs GCB-DLCBL cell lines. 16 In contrast, CC-122 exhibited antiproliferative activity in both ABC-and GCB-DLBCL cell lines; thus, we wanted to explore the potential difference in the underlying mechanisms for the differential effects exhibited by the 2 drugs.…”
Section: Differential Activities Of Cc-122 and Lenalidomide In Dlbclmentioning
confidence: 93%
“…Although early reports of treatment with DA‐EPOCH‐R in patients with MYC‐associated lymphomas are encouraging, we sought to augment this by incorporating lenalidomide specifically into the treatment of patients with DHL and DEL. Lenalidomide is an immunomodulatory drug with single‐agent activity in patients with recurrent/refractory DLBCL . In treatment‐naive settings, lenalidomide has been combined successfully with R‐CHOP and has demonstrated provocative activity, particularly in the high‐risk nongerminal center subtype of DLBCL, which encompasses the majority of patients with DEL .…”
Section: Introductionmentioning
confidence: 99%
“…Studies with rituximab-bendamustine in patients who were ineligible for, or have failed ASCT reported ORR of 45-62% and CR rates of 15-37% (Ohmachi et al, 2013;Vacirca et al, 2014). Lenalidomide with or without rituximab was shown to induce ORR of 27% and CR rates of 10-15% in patients with relapsed/refractory DLBCL, albeit that the benefit of lenalidomide may be seen preferentially in the non-GCB DLBCL subtype (Hernandez-Ilizaliturri et al, 2011;Czuczman et al, 2017). The subjective toxicity of the R-PECC regimen was considered very mild in our patient series.…”
Section: Discussionmentioning
confidence: 99%